A personal history of CESR and CLEO - Berkelman, K (World Scientific, 2004)
Includes bibliographical references (p. 147-148) and index.; A historical account of the CESR and CLEO from their beginnings in the late 1970s until the end of data collection at particle energies above the threshold for B meson production in June 2001. The CESR electron-positron collider was the culmination of a series of electron accelerators constructed at the Cornell Laboratory of Nuclear Studies, starting in 1945. Measurement of the products of the e+e- collisions was performed with the multipurpose CLEO apparatus, built and operated by the CLEO collaboration, which consisted of about 200 faculty, staff and graduate students from over 20 universities. This account is based mainly on the author's recollections as a participant